Resonances and lattice field theory - MacMaghnusa, Darran (Trinity College (Dublin, Ireland). School of Mathematics, 2012)
In this thesis, we look at the extraction of resonance parameters in lattice field theory. In particular we detail two major methods of dealing with resonances and consider them in a perturbative and nonpertnrbative context. We also explore a third method in less detail in a nonpertnrbative context. The first method is the well known Liischer's method, which relates the infinite volume phase shift, δ(p), of two particle scattering states to the energies of those states in a finite volume. It is po.ssible to extract resonance parameters via a fit to some expre.ssion for phase shift.
Keywords: Mathematics, Ph.D.; Ph.D. Trinity College Dublin.